2018
DOI: 10.1080/15384101.2018.1486166
|View full text |Cite
|
Sign up to set email alerts
|

Sirt7 inhibits Sirt1-mediated activation of Suv39h1

Abstract: Sirtuins regulate a variety of cellular processes through protein deacetylation. The best-known member of mammalian sirtuin family, Sirt1, plays important roles in the maintenance of cellular homeostasis by regulating cell metabolism, differentiation and stress responses, among others. Sirt1 activity requires tight regulation to meet specific cellular requirements, which is achieved at different levels and by specific mechanisms. Recently, a regulatory loop between Sirt1 and another sirtuin, Sirt7, was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In addition to Sirtuins, there are other epigenetic modification enzymes, including SUV39H1 and EZH2 are involved in insulin resistance and T2DM (271276). There is an interaction between SUV39H1 and Sirtuins, including SIRT1, SIRT3, and SIRT7 (277281). EZH2 is reportedly the deacetylating substrate of SIRT1 (282, 283).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Sirtuins, there are other epigenetic modification enzymes, including SUV39H1 and EZH2 are involved in insulin resistance and T2DM (271276). There is an interaction between SUV39H1 and Sirtuins, including SIRT1, SIRT3, and SIRT7 (277281). EZH2 is reportedly the deacetylating substrate of SIRT1 (282, 283).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there was no significant difference in H3K9me3 levels in the promoter of complement C3, which indicated that direct histone methylation was not the main mechanism of Suv39h1’s effect on complement C3. Instead, one possible mechanism is that Suv39h1 depletion suppresses H3K9me3 in the promoter of peroxisome proliferator–activated receptor γ (PPARγ), leading to an increase in PPARγ expression, which then down‐regulates complement C3 levels indirectly …”
Section: Discussionmentioning
confidence: 99%
“…Genes 2021, 12, x FOR PEER REVIEW 2 of 14 activity of numerous histone modifiers such as methytransferases and acetyltransferases [8,9]. Notwithstanding, sirtuins control the activity and functions of enzymes, transcription factors, and other chromatin unrelated molecules mainly through direct deacetylation, highlighting their complex functions in the regulation of cellular processes [3].…”
Section: Mammalian Sirtuins: General Functions and Activation In Response To Stressmentioning
confidence: 99%
“…The ability of sirtuins to control such a broad range of biological functions mainly derives from their capacity to control both chromatin-related and -unrelated targets. Sirtuins act as potent epigenetic silencers by promoting heterochromatin formation through the direct deacetylation of different histone marks or indirectly by controlling the activity of numerous histone modifiers such as methytransferases and acetyltransferases [ 8 , 9 ]. Notwithstanding, sirtuins control the activity and functions of enzymes, transcription factors, and other chromatin unrelated molecules mainly through direct deacetylation, highlighting their complex functions in the regulation of cellular processes [ 3 ].…”
Section: Mammalian Sirtuins: General Functions and Activation In Response To Stressmentioning
confidence: 99%
See 1 more Smart Citation